Determinación de costos y rendimiento para la producción de cuyes en la propiedad de cuyes en la propiedad de la familia Cabrera Piedra en la parroquia Urdaneta cantón Saraguro. - Cabrera Piedra, Sylvia Johanna (2022)
This work is aimed at the development of the production of non-traditional products such as raising guinea pigs, in addition to determining the costs and performance of guinea pig production in a technical way in the community of BAHIN, Urdaneta parish of the canton SARAGURO. This budget was made by quarters to determine the investment. In the first quarter, is a total investment of $4,228.14 dollars, and in the fourth quarter there is an amount of $4,288.01 dollars. In addition, it was concluded that the unit cost of producing a guinea pig was $8.36 dollars in the first quarter and for the following quarters, the cost will increase due to the increase in the number of animals, concluding that the cost-benefit ratio of $1.16 is $0.16 cents which means that for every dollar invested we recover $0.16 cents. The raising of guinea pigs has always been done in a traditional way, which consists, of wood boxes built inside of the kitchen where they are mixed with other animals, this animal husbandry often has poor hygiene and health standards, so, based on this data is intended to determine the cost of producing guinea pigs in a technical way. Therefore, apply specialized techniques to obtain greater profitability and higher yields in the production of these animals, as well as minimize the waste of resources and reduce costs production. Therefore, it is of great importance to work on different studies related to sanitary maintenance, food, and health in such a way that the production systems can be efficient, also, by implementing new strategies is possible to improve production and make it costefficient and take advantage most of the available resources and management based on costs. In the near future, we look for a database that can help us calculate production cost more effectively through the use of records and economic formats that can serve as strategies to generate more profits